Developing Non-Positional Teacher Leadership of Formative Assessment Practices: Findings from the Teacher-Led Learning Circles Project - Campbell, Carol; DeLuca, Christopher; LaPointe-McEwan, Danielle; Rickey, Nathan; Ceau, Maeva (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2025)
This article examines the development of teacher leadership through the Teacher-Led Learning Circles project, a professional learning and research initiative across seven countries: Brazil, Côte d’Ivoire, Ghana, Malaysia, South Korea, Switzerland, and Uruguay. Through targeted professional development over one academic year, the project advanced non-positional teacher leadership and confidence in four core formative assessment strategies as well as the embedded use of these strategies by teachers. Data were collected through multiple sources, including a teacher pre-survey (n = 171), a teacher post-survey (n = 121), a teacher codification framework questionnaire (n = 113), a local facilitator questionnaire (n = 27), a local union representative questionnaire (n = 10), a national researcher questionnaire (n = 7), and seven country profiles. Findings show that when teachers are supported, their influence grows, and formative assessment practices become more embedded and confident, highlighting the potential of teacher-led professional development for sustainable educational improvement.